Polled Bali Cattle and Potentials for the Development of Breeding Industry in Indonesia - Sudirman Baco; Zulkarnain; Ratmawati Malaka; Gozali R Moekti (Hasanuddin Journal of Animal Science (HAJAS), 2020)
A polled Bali Cattle, or a naturally hornless cattle breed was first recognized in the early 1980s in Sidendreng-Rappang (Sidrap), south Sulawesi, where Bali cattle (Bos sondaicus) herd were mixreared with some Brahman cross (BX). Whereas BX is the result of a cross between a Brahman cattle and the Hereford or shorthorn (Bos Taurus) breed on a commercial ranch in the region. As such a variant is considered as having high productivity trait advantages and/or as even possibly becoming a superior cattle breed of choice being able to develop by the University of Hassanuddin, various researches had been carried out since 1985. To date, the research works had resulted in some findings, however, there might have only been up to preliminary stages so far. Vast and thorough investigations on productivity traits of the polled Bali cattle (PBC) variants are being sought. Currently, a science and technology-based local cattle breeding industry development program at the Maiwa breeding center, Faculty of Animal Husbandry, Hasanuddin University has been carrying out serial studies on genetic profiles of the variants, and also on their growth control and adaptation genes. The genes have been targeted for use as marker-assisted selection (MAS).